Effect of shelf life on IL6 and CD62P thrombosite consentrate levels (Experimental Study at UDD PMI Semarang City) - Diah Hastuti (Publikasi Indonesia, 2023)
Thrombocyte concentrate is a blood product that is labile and easily damaged by its blood cells. Storage time is expected to cause changes in several conditions so that it will affect the quality of TC which can affect levels CD62P and levels interleukins 6 (IL-6). The purpose of this research is to determine the effect of the length of storage of thrombocyte concentrate (TC) on IL-6 levels and CD62P levels in UDD PMI Semarang City. This research is research experimental, where this study analyzes how changes in levels IL-6 and CD62P levels on TC based on length of storage at PMI Semarang Blood Donor Unit. The research design was divided into groups on day 0, day 1, day 3, day 5 and day 7. Population in this study were 5 TC bags produced and stored at the PMI Blood Donor Unit in Semarang City. The research sample consisted of 5 TC bags using purposive sampling technique. IL-6 levels were analyzed using the ELISA method. Examination of CD62P Levels use flow cytometer device. IL-6 levels were tested differently using repeated ANOVA and continued with the LSD Post Hoc test to show differences between groups (P<0.05). For CD62P, the data were analyzed using the Friedman test and followed by the Wilcoxon test to show differences between groups (P<0.05). The research results show that the lowest levels of IL-6 and CD62P in TC were found on day 0 and the highest levels of IL-6 and CD62P in TC were found on day 7.